MELHORIAS TRAZIDAS PELA IMPLEMENTAÇÃO DO PLANEJAMENTO ESTRATÉGICO EM UMA MICRO EMPRESA: ESTUDO DE CASO DO ALFA RESTAURA - Flávia Oliveira Araujo, Livia; Fernandes Martins, Vidigal (LINKSCIENCEPLACE, 2026)
The paper aims to identify business problems ALFA Restaurant proposing improvement actions undertaken with a specific strategic planning. The branch of the business carried on by the organization is to provide service and food trade. There is fierce competition in this sector of activity, hence the importance of developing a strategic quality planning aimed at achieving rapid decision-making, administrative and accounting organization to enable efficient response when it comes to serving customers and suppliers and, most importantly, achieve the goals set by administrators. This paper develops the theoretical framework, which addresses the key concepts inherent in the proposed issue, as the concept of planning, strategic planning and entrepreneurial profile. Then the practical part, where the company’s objectives, goals, mission, analysis of the internal and external environment were described by showing a brief history of the organization and presentation of your competitors is presented. In conclusion the relationship between theory and practice is shown by proposing alternatives available in the theory of strategic planning for the organization (or other small business), showing the hardships and the contribution of labor to the science of Directors.